Multivalent S-sialoside protein conjugates block influenza hemagglutinin and neuraminidase. (29th November 2016) - Yang, Yang; Liu, Hai-Peng; Yu, Qun; Yang, Mei-Bing; Wang, De-Min; Jia, Tian-Wei; He, Hao-Jie; He, Yun; Xiao, Hai-Xia; Iyer, Suri S.; Fan, Zhen-Chuan; Meng, Xin; et al.
Abstract: A new class of S-sialoside Human Serum Albumin (HSA) and Bovine Serum Albumin (BSA) conjugates were prepared to enhance the binding affinity to hemagglutinin (HA) and neuraminidase (NA). The valency of glycoconjugates was controlled by the reaction ratio of the S-sialoside monomer and protein. Hemagglutination inhibition assay showed that these synthetic glycoproteins have higher affinity to HA than the small clusters of sialosides with lower valency, due to multivalent effect and optimized three dimensional presentation of sialosides on the protein platform. The results of fluorescent NA inhibition assay showed that some of the conjugates have moderate NA inhibitory activity, in comparison to the monomer and low valent conjugates with weak or none inhibitory activity. These synthetic sialylated proteins were not cytotoxic with concentrations up to 100 μM, since the sialylation did not change the secondary structure of protein. This new kind of conjugates can be used as lead compounds for antiviral drug design and the construction of pseudo sialoside-protein conjugates library to investigate the carbohydrate-HA/NA recognition process and a platform for the influenza virus capturing. Graphical abstract: Highlights: Di-, tri- and tetra-valent S-sialosides as moderate NA inhibitors were synthesized. Different density of S-sialoside coated protein as potent HA inhibitor were prepared. Sialylation of proteins does not change their secondary structures. The conjugates showed no cytotoxicity with the concentrations up to 100 μM.